Implementasi Projek Penguatan Profil Pelajar Pancasila Market Day sebagai Karakter Kewirausahaan - Aminah, Siti; Rondli, Wawan Shokib (Peneliti.net, 2025)
The purpose of this study is to analyse the implementation of P5 Market Day as an entrepreneurial character in fourth grade students of SD 4 Sadang. This type of research uses qualitative research with the narrative inquiry method and covers the implementation of the Pancasila Student Profile Strengthening Project (P5) Market Day activities at SD 4 Sadang. Data collection techniques through interviews, observation, and documentation. The subjects of this study were fourth grade students of SD 4 Sadang and fourth grade teachers of SD 4 Sadang with a total of 15 students. Data analysis techniques in this study consist of data collection, data reduction, data presentation, and conclusion drawing or verification. Based on the results of this study, it can be concluded that the implementation of the Pancasila Student Profile Strengthening Project (P5) through market day activities fosters entrepreneurial character in students. Market day activities get a positive response from class IV students of SD 4 Sadang. Although in the implementation of market day activities there are still many shortcomings and obstacles, the school, especially the class teacher, can still carry out market day activities tailored to the abilities of students. The value of entrepreneurial character that is realised is achievement motivation, entrepreneurial leadership, and responsiveness and creativity.